Stress Hormones: Emerging Targets in Gynecological Cancers - Chen, Guoqiang; Qiu, Lei; Gao, Jinghai; Wang, Jing; Dang, Jianhong; Li, Lingling; Jin, Zhijun; Liu, Xiaojun (Frontiers in Cell and Developmental Biology, 2021)
In the past decade, several discoveries have documented the existence of innervation in ovarian cancer and cervical cancer. Notably, various neurotransmitters released by the activation of the sympathetic nervous system can promote the proliferation and metastasis of tumor cells and regulate immune cells in the tumor microenvironment. Therefore, a better understanding of the mechanisms involving neurotransmitters in the occurrence and development of gynecological cancers will be beneficial for exploring the feasibility of using inexpensive β-blockers and dopamine agonists in the clinical treatment of gynecological cancers. Additionally, this article provides some new insights into targeting tumor innervation and neurotransmitters in the tumor microenvironment.